Cooperative Integrated Reading and Composition (CIRC) and Learning Activeness: Their Effect on Students’ Reading Comprehension in Junior High School - Dwi Wahyuni, Aelista; Yukamana, Hanni; Mulyadi, Mulyadi (FOSTER: Journal of English Language Teaching, 2025)
This study examines the effect of the Cooperative Integrated Reading and Composition (CIRC) method and students’ learning activeness on the reading comprehension of seventh-grade students at SMPN 3 Rantau Bayur. Using a quantitative experimental design, two groups were involved: an experimental group taught with CIRC and a control group taught using conventional methods. Students in each group were further classified into high and low learning activeness categories. Data were collected through pre-tests and post-tests for reading comprehension, and learning activeness was assessed through observation checklists. The results, analyzed using Two-Way ANOVA, indicated that: (1) the CIRC method significantly improved students’ reading comprehension, (2) learning activeness had a significant positive effect on reading comprehension, and (3) there was no significant interaction between the teaching method and learning activeness. These findings suggest that both CIRC and learning activeness independently contribute to better reading comprehension, making CIRC an effective strategy for enhancing reading skills in junior high school students.